Fragmentation can increase spatial genetic structure without decreasing pollen-mediated gene flow in a wind-pollinated tree - WANG, RONG; COMPTON, STEPHEN G.; CHEN, XIAO-YONG (Molecular ecology, 2011)
Fragmentation reduces population sizes, increases isolation between habitats and can result in restricted dispersal of pollen and seeds. Given that diploid seed dispersal contributes more to shaping fine‐scale spatial genetic structure (SGS) than haploid pollen flow, we tested whether fine‐scale SGS can be sensitive to fragmentation even if extensive pollen dispersal is maintained. Castanopsis sclerophylla (Lindley & Paxton) Schottky (Fagaceae), a wind‐pollinated and gravity seed‐dispersed tree, was studied in an area of southeast China where its populations have been fragmented to varying extents by human activity. Using different age classes of trees in areas subject to varying extents of fragmentation, we found no significant difference in genetic diversity between prefragmentation vs. postfragmentation C. sclerophylla subpopulations. Genetic differentiation among postfragmentation subpopulations was also only slightly lower than among prefragmentation subpopulations. In the most fragmented habitat, selfing rates were significantly higher than zero in prefragmentation, but not postfragmentation, cohorts. These results suggest that fragmentation had not decreased gene flow among these populations and that pollen flow remains extensive. However, significantly greater fine‐scale SGS was found in postfragmentation subpopulations in the most fragmented habitat, but not in less fragmented habitats. This alteration in SGS reflected more restricted seed dispersal, induced by changes in the physical environments and the prevention of secondary seed dispersal by rodents. An increase in SGS can therefore result from more restricted seed dispersal, even in the face of extensive pollen flow, making it a sensitive indicator of the negative consequences of population fragmentation.